Caregiver profiles in dementia related to quality of life, depression and perseverance time in the European Actifcare study: the importance of social health. (2nd January 2017) - Janssen, Eveline P.C.J.; de Vugt, Marjolein; Köhler, Sebastian; Wolfs, Claire; Kerpershoek, Liselot; Handels, Ron L.H.; Orrell, Martin; Woods, Bob; Jelley, Hannah; Stephan, Astrid; Bieber, Anja; Meyer, Gabriele; et al.
ABSTRACT: Objectives: To identify caregiver profiles of persons with mild to moderate dementia and to investigate differences between identified caregiver profiles, using baseline data of the international prospective cohort study Actifcare. Methods: A latent class analysis was used to discover different caregiver profiles based on disease related characteristics of 453 persons with dementia and their 453 informal caregivers. These profiles were compared with regard to quality of life (CarerQoL score), depressive symptoms (HADS-D score) and perseverance time. Results: A 5-class model was identified, with the best Bayesian Information Criterion value, significant likelihood ratio test ( p < 0.001), high entropy score (0.88) and substantive interpretability. The classes could be differentiated on two axes: (i) caregivers' age, relationship with persons with dementia, severity of dementia, and (ii) tendency towards stress and difficulty adapting to stress. Classes showed significant differences with all dependent variables, and were labelled 'older low strain', 'older intermediate strain', 'older high strain', 'younger low strain' and 'younger high strain'. Conclusion: Differences exist between types of caregivers that explain variability in quality of life, depressive symptoms and perseverance time. Our findings may give direction for tailored interventions for caregivers of persons with dementia, which may improve social health and reduce health care costs.